2008
DOI: 10.1038/ejhg.2008.245
|View full text |Cite
|
Sign up to set email alerts
|

The PDGF-C regulatory region SNP rs28999109 decreases promoter transcriptional activity and is associated with CL/P

Abstract: Human linkage and association studies suggest a gene(s) for nonsyndromic cleft lip with or without cleft palate (CL/P) on chromosome 4q31 -q32 at or near the platelet-derived growth factor-C (PDGF-C) locus. The mouse Pdgfc À/À knockout shows that PDGF-C is essential for palatogenesis. To evaluate the role of PDGF-C in human clefting, we performed sequence analysis and SNP genotyping using 1048 multiplex CL/P families and 1000 case-control samples from multiple geographic origins. No coding region mutations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 45 publications
1
38
1
2
Order By: Relevance
“…56 Further analysis of this regulatory region revealed that these differences in the PDGFC promoter lead to a decrease in expression using reporter assays to examine gene expression. 56 This association is the first described linkage to a human birth defect with reduced PDGF signaling and hints at another etiology for cleft palate in human populations.…”
Section: Resultsmentioning
confidence: 99%
“…56 Further analysis of this regulatory region revealed that these differences in the PDGFC promoter lead to a decrease in expression using reporter assays to examine gene expression. 56 This association is the first described linkage to a human birth defect with reduced PDGF signaling and hints at another etiology for cleft palate in human populations.…”
Section: Resultsmentioning
confidence: 99%
“…Missense mutations in the PDGFRA-coding region that alter amino acids within the fourth immunoglobulin domain of the extracellular portion of the receptor, the transmembrane domain, or the cytoplasmic domain C-terminal to the tyrosine kinase domains as well as single base-pair substitutions in the 3 ′ untranslated region (UTR) are associated with nonsyndromic cleft palate (Rattanasopha et al 2012). Moreover, single-nucleotide polymorphisms in the PDGFC regulatory region that repress transcriptional activity of the promoter are associated with cleft lip and palate (Choi et al 2009). In the case of PDGFRB, heterozygous missense mutations that modify amino acids in the juxtamembrane and tyrosine kinase domains cause Kosaki overgrowth syndrome (OMIM 616592) and Penttinen syndrome (OMIM 601812), respectively, both of which are characterized by facial dysmorphism and fragile skin, among other defects (Johnston et al 2015;Takenouchi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, great efforts have been taken to unravel genetic background leading to its pathogenesis [Grant et al, 2009]. Several potentially causal genes have been identified, such as IRF6 [Zucchero et al, 2004], MSX1 [Van den Boogaard et al, 2008], TGFB3 [Reutter et al, 2008], TGFA , PDGFC [Choi et al, 2009], PVRL1 [Avila et al, 2006], FGFs [Riley and Murray, 2007], TBX22 [Pauws et al, 2009], among which the interferon regulatory factor 6, IRF6 on chr. 1q32, has the most supporting data.…”
Section: Introductionmentioning
confidence: 99%